MODEL PEMBELAJARAN AKTIF MATA KULIAH PRAKTIK PEDALANGAN GAYA JAWA TIMURAN - Sudarsono, S., (Institut Seni Indoensia Surakarta, 2016)
This article is squeezed from the research class action entitled â€œActive Learning Model CourseÂ Practice Puppetry East Javanese Styleâ€. The study was conducted in order to evaluate the success ofÂ the learning process and determine the effectiveness of the learning model that has been applied, inÂ order to determine the extent of the success of a process that has lasted learning. It was important toÂ remember the era of the development of competency-based curriculum that is implemented from 2008Â to 2013, special courses have not been evaluated. The method used in the study of this class action isÂ syntaxmatic development, which is implemented in an active learning model for the course ofÂ Practice Puppetry East Java style. The first stage is to establish a climate of inclusion. The secondstage; lecturers provide an alternative example in accordance with the work on the topic of teachingÂ materials in the face of it. The third stage is to make a decision of personal value. The fourth stage isÂ to identify courses of action. In the process of learning and teaching faculty should be able to makethe atmosphere is not boring to the students, therefore, lecturers wherever possible to consider theÂ classroom atmosphere and the character of the students. The fifth stage; students make generalÂ comments on the matter and the steps that have been made. The last stage is the follow-up behavior.From the experience that has been lived for more than five semesters, students are expected to showÂ the positive behavioral change that is better than before. The learning process is essentially a systemÂ of teaching and learning is an integral inseparable from the system the involvement of elements otherlearning. Therefore, in the model of syntaxmatic development can not be separated also from otherÂ learning systems such as: system response and support system.Keywords: Learning model, puppetry, style, East Java.